Metal Additive Manufacturing - Lancaster, Robert J.; Fortunato, Alessandro; Kolisnychenko, Stanislav (Specialized collections, 2020)
This volume is the first part of a specialised series on "Additive Manufacturing" consisting of papers published by Trans Tech Publications Inc. during the period of 2018 - 2019. This collection of scientific papers describes a wide range of engineering approaches and solutions in the area of additive manufacturing technologies for metallic materials. Additive Manufacturing, Rapid Prototyping, 3D Printing, Powder Bed Fusion, Direct Energy Deposition, Selective Laser Melting, Selective Laser Sintering, Electron Beam Melting, Direct Metal Laser Sintering, Selective Laser Cladding, Cold Spray, Powder, Alloys, Metal Matrix Composites, Wire Arc Additive Manufacturing, Laser Metal Deposition, Process Parameters, Post-Processing, Indirect 3D Printing, Direct 3D Printing, Modelling, Microstructure, Mechanical Properties.